Longitudinal association among endothelial function, arterial stiffness and subclinical organ damage in hypertension. (15th February 2018) - Tomiyama, Hirofumi; Ishizu, Tomoko; Kohro, Takahide; Matsumoto, Chisa; Higashi, Yukihito; Takase, Bonpei; Suzuki, Toru; Ueda, Shinichiro; Yamazaki, Tsutomu; Furumoto, Tomoo; Kario, Kazuomi; Inoue, Teruo; et al.
Abstract: Objectives: To examine the longitudinal mutual association between endothelial dysfunction and arterial stiffness, and also to determine which of the two variables was more closely associated with the progression of subclinical organ damage. Methods: The brachial-ankle pulse wave velocity (baPWV), carotid intima-media thickness (CIMT), estimated glomerular filtration rate, microalbuminuria and flow-mediated vasodilatation of the brachial artery (FMD) were measured three times at 1.5-year intervals in 674 Japanese patients receiving antihypertensive treatment. Results: The change of the baPWV during the study period was larger in the subjects with baseline FMD values in the lowest tertile as compared to those with baseline FMD values in the highest tertile. The change of the CIMT was smaller in the subjects with baseline baPWV values in the lowest tertile than in those with baseline baPWV values in the highest tertile. After the adjustment, the FMD value at the baseline was inversely associated with the baPWV at the end of the study period (beta = − 0.07, p = 0.01), although, the reverse association was not significant. The baPWV, but not the FMD value, at the baseline was associated with the CIMT (beta = 0.06, p = 0.04) measured at the end of the study period. Conclusions: In hypertension, endothelial dysfunction was associated with the progression of arterial stiffness, although the reverse association was not confirmed. The increased arterial stiffness rather than endothelial dysfunction may be more closely associated with the progression of atherosclerotic vascular damage, and the endothelial dysfunction-arterial stiffness-atherosclerosis continuum may be important in hypertension.